Entrapment Neuropathies in the Upper and Lower Limbs: Anatomy and MRI Features - Qian Dong; Jon A. Jacobson; David A. Jamadar; Girish Gandikota; Catherine Brandon; Yoav Morag; David P. Fessell; Sung-Moon Kim (Radiology Research and Practice)
Peripheral nerve entrapment occurs at specific anatomic locations. Familiarity with the anatomy and the magnetic resonance imaging (MRI) features of nerve entrapment syndromes is important for accurate diagnosis and early treatment of entrapment neuropathies. The purpose of this paper is to illustrate the normal anatomy of peripheral nerves in the upper and lower limbs and to review the MRI features of common disorders affecting the peripheral nerves, both compressive/entrapment and noncompressive, involving the suprascapular nerve, the axillary nerve, the radial nerve, the ulnar nerve, and the median verve in the upper limb and the sciatic nerve, the common peroneal nerve, the tibial nerve, and the interdigital nerves in the lower limb.